English: English - Ramkita, Nora; Krisna Murti; Citra Dewi (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
Background A frozen section or vries coupe (VC) is an examination procedure performed by a pathologist during a patient operation on the surgical table. VC provides immediate information to surgeons regarding the benign or malignant status of a tissue, as well as determines the incision margin free from tumor mass. Objective This study aimed to evaluate diagnostic accuracy using the slide preparation archives of VC and histopathology at the Anatomic Pathology Department of Dr. Mohammad Hoesin Central General Hospital (RSUP), Palembang. Methods: Samples of patients were collected from 1 January 2021 to 1 October 2023, while sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for VC were assessed compared to the definitive diagnosis of histopathology. A reassessment was conducted by two pathologists on slide preparations with unmatched results between VC and histopathological diagnosis. Result VC examination showed sensitivity, specificity, PPV, and NPV of 99.7%, 99.7%, 98.3%, and 98.3% for benign tumors as well as 98%, 99.6%, 98.3%, and 98.3% for malignant tumors, respectively. The reassessment of the inappropriate slide preparations obtained a weighted kappa value of 0.586, signifying moderate agreement. Diagnostic discordance is caused by the experience of pathologists, freezing artifacts, and challenges in obtaining precise samples under a limited timeframe. Conclusion This study provided valuable insights into the effectiveness of VC procedure in intraoperative tissue diagnosis, showing the need for collaborative efforts and experienced pathologists to achieve improved accuracy.